Virtual Laboratory: Innovation and Its Impact on Students' Motivation and Interest in Learning - Siti Nurlaili; Tiara Dwi Saiva; M. Fadhil Khairullah (Indonesian Publication Center, 2024)
The development of digital technology has driven various innovations in science education, one of which is the use of virtual laboratories. This study aims to analyze the implementation of virtual laboratories in science learning and examine their influence on students’ motivation and interest in learning. The method used was a systematic literature review with a qualitative descriptive approach. Data were collected through searches in reputable electronic databases using relevant keywords and limited to publications from 2015 to 2024. The initial search identified 37 articles, which were then screened through the stages of identification, screening, eligibility, and inclusion, resulting in 19 articles that met the criteria. The data were analyzed using thematic analysis to identify patterns of virtual laboratory implementation and their impacts on students’ affective and cognitive aspects. The findings indicate that virtual laboratories consistently contribute to improving learning motivation, learning interest, conceptual understanding, and learning outcomes at the junior high school, senior high school, and higher education levels. Interactive simulations such as PhET are able to create an engaging, flexible, safe learning environment and encourage independent exploration, thereby increasing students’ active participation. However, their effectiveness is influenced by technological readiness, teacher competence, digital literacy, and institutional support. Therefore, virtual laboratories are not only an alternative to conventional practicum activities but also a strategic pedagogical instrument in supporting the transformation of science learning in the digital era.